A7: Initial Assessment of Multi‐biomarker Disease Activity Assay in JIA. Issue 11 (March 2014) - Ringold, Sarah; Lu, Lucy; Wallace, Carol A.; Sasso, Eric H.; Scott Eastman, P.
Abstract : Background/Purpose: Current measures of disease activity in JIA, including physician global assessment of disease activity and active joint count, are subjective and potentially confounded by disease heterogeneity and comorbid conditions. A multi‐biomarker disease activity assay (MBDA) incorporating a panel of biomarkers may provide objective and quantitative data regarding disease activity that would be of great value to physicians caring for children with JIA. The objective of this investigation was to measure the feasibility of a MBDA developed for RA (Vectra DA, Crescendo Bioscience, Inc), and its individual biomarker components as a measure of disease activity in patients with JIA. Methods: Samples were analyzed from a prior cross‐sectional, observational study that included 31 children with rheumatoid factor (RF) positive polyarticular JIA (n = 4), RF negative polyarticular JIA (n = 18), or extended oligoarticular JIA (n = 8). All children had established disease and were on treatment (mean disease duration 5 years; range 0–15 years). The Juvenile Arthritis Disease Activity Score (JADAS) based on 10 joints was calculated for each sample and each sample was classified as clinically inactive disease or active disease using the ACR provisional criteria for clinically inactive disease (CID). Samples were analyzed for 18 individual biomarkers, 12 of which comprise Vectra DA and a total Vectra DA score was calculated. Biomarker assays were also performed for a cohort of 44 healthy 18 year‐old controls obtained from the ProMeDx specimen bank. Results: The mean JADAS value for the cohort was 4.9 (range 0–16.3). The mean Vectra DA score for the healthy controls was 14 (maximum possible score is 100). The mean score was 20 for the children with CID, and 27 for children with active disease. The correlation between the Vectra DA and JADAS was moderate (r = 0.68; Figure 1). The individual biomarker profiles for the control cohort and the children who met criteria for inactive disease appeared similar, but several individual biomarkers, including SAA, CRP, IL‐6 and MMP‐3 were elevated in the active disease group as compared to the children with CID and controls (Figure 2). Conclusion: These data support the feasibility of the development of a JIA‐specific MBDA that will reflect the underlying heterogeneity of the disease process and provide physicians with an objective measure of disease activity. Additional analyses of larger sets of biomarkers using samples with a broad range of disease activities will inform the next steps of assay development.